Data-driven thermal analysis of indoor cooling for a thermoelectric radiant panel systemMendeley Data - Muhammad ‘Amir Roslan; Farah Liana Mohd Redzuan (Data in Brief)
A thermal analysis of a thermoelectric radiant panel (TERP) system was conducted to evaluate its cooling effectiveness in maintaining indoor comfort within the temperature range recommended by ASHRAE Standard 55 and Malaysian Standard (MS) 1525 under tropical climate conditions. The study utilized ANSYS software, incorporating computational fluid dynamics (CFD) tools for detailed heat transfer simulations. The analysis examined the impact of outdoor temperature variations on indoor conditions and TERP system panel temperatures by considering heat transfer mechanisms, boundary conditions, and material properties to ensure accuracy. By accounting for these factors, the simulation provided a realistic representation of the thermal environment in a tropical climate. The simulation results were visualized as 3D thermal profiles, with color contours illustrating temperature distributions across the panel surface and the indoor environment. The collected data was then simplified into graph form for easier interpretation and analysis, including an evaluation of compliance with thermal comfort standards such as ASHRAE Standard 55 and MS 1525. The findings serve as a benchmark for assessing thermoelectric cooling performance in tropical buildings and offer valuable insights for optimizing thermoelectric cooling systems in similar climates. This study contributes to the development of sustainable cooling solutions and supports further research in thermoelectric cooling applications.